UJI IRITASI SEDIAAN KRIM EKSTRAK ETANOL DAUN CENGKEH (Syzygium aromaticum L.) TERHADAP MENCIT (Mus musculus) - Azis, Arief; Fauzan Nursyawal (Akademi Farmasi Yamasi Makassar, 2024)
This study aims to determine the irritating effect of clove leaf ethanol extract cream (Syzygium aromaticum L.) on mice (Mus musculus) and at what concentration clove leaf extract (Syzygium aromaticum L.) can cause irritation in mice (Mus musculus). Clove leaf extract was prepared in cream preparations with a concentration of 10% and 11%. This test used a laboratory experimental method carried out at the Pharmacology Laboratory of the Yamasi Pharmacy Academy Makassar, then tested the irritating effect of Clove Leaf Extract Cream (Syzygium aromaticum L.) using the draize method on mice (Mus musculus) as test animals and observed for 24 hours,48 hours, 72 hours. Then observed the appearance of erythema and edema that occurred at each concentration of preparations in mice (Mus musculus). Based on the results of the study, it can be concluded that the ethanol extract cream of clove leaves (Syzygium aromaticum L.) at concentrations of 10% and 11% does not cause irritation.